Mast cells as indicators of foreign particle biocompatibility - O. S. Artashyan; Yu. S. Khramtsova; A. A. Vlasova; N. V. Tyumentseva; B. G. Yushkov (Медицинская иммунология, 2024)
The key problem of introducing nanoparticles into clinical practice for diagnostic and therapeutic purposes is their safety. Connective tissue, an important component of which are mast cells, reacts actively in response to foreign particles. The reaction of mast cells can be an indicator of the biocompatibility of foreign particles. The study was conducted on male Wistar rats. Iron-carbon nanoparticles in the FeC modification stabilized in an aqueous medium using an auxiliary substance were used. Tissue examination (liver, lungs, heart, thymus, kidneys) was performed 1, 7 and 30 days after injection. After the injection of nanoparticles, the largest quantity of them is found in the liver and lungs, a smaller quantity is found in the heart, kidneys and thymus. The liver and lungs are the main organs of excretion of nanoparticles due to phagocytes. The accumulation of nanoparticles in the liver leads to the development of destructive processes and to the activation of compensatory and adaptive mechanisms in the form of cellular and intracellular regeneration of hepatocytes. In organs with a low content of nanoparticles, structural changes are poorly expressed. The mast cells of the studied organs react differently to the introduction of nanoparticles. The first to react are the mast cells of the liver by reducing the quantity and increasing degranulation. The population of lung mast cells reacts unidirectionally by sharply activating degranulation without changing the amount. An increase in the secretory activity of mast cells in the lungs and liver indicates the participation of mast cells in the regulation of particle elimination through intercellular signaling pathways of interaction with the system of phagocytic mononuclear cells. Heart mast cells are involved in maintaining the inflammatory process in the early period of the experiment, contribute to the return of myocardial parameters to homeostatic norm in the late period of the experiment. Mast cells can be considered as indicators of biocompatibility nanoparticles. The absence of an inflammatory process and the preservation of the structural and functional characteristics of the tissues where nanoparticles accumulate, as well as the reaction of mast cells in them, indicate the relative safety of the particles under study.